CIPP Evaluation Method for the Scout Extracurricular Program Management - Aditya Wibowo; Jajang Dede Mulyani (Physical Activity Journal)
The Scout extracurricular program is an activity outside of regular school hours that focuses on developing character, skills, and leadership through outdoor activities and social interactions. The evaluation of the Scout Extracurricular Program Managementis essential to ensure that the program effectively meets the developmental needs of participants and fosters valuable life skills. This research aims to determine the management of the scouting extracurricular program and evaluate the management. The research method is descriptive qualitative research with data collection methods through interviews, observation, and documentation. The sampling method uses snowball sampling. The research data were analyzed through data reduction, presentation, and conclusion drawing. The research reveals that the management of scouting extracurricular programs includes Context, Input, Process, and Product. The evaluation includes delivering extracurricular planning results to parents/guardians, conditioning the implementation of routine training activities, evaluating extracurricular goal indicators, and assessing students